12.5% Flexible Nonfullerene Solar Cells by Passivating the Chemical Interaction Between the Active Layer and Polymer Interfacial Layer. Issue 22 (17th January 2019) - Xiong, Sixing; Hu, Lin; Hu, Lu; Sun, Lulu; Qin, Fei; Liu, Xianjie; Fahlman, Mats; Zhou, Yinhua
Abstract: Nonfullerene (NF) organic solar cells (OSCs) have been attracting significant attention in the past several years. It is still challenging to achieve high‐performance flexible NF OSCs. NF acceptors are chemically reactive and tend to react with the low‐temperature‐processed low‐work‐function (low‐WF) interfacial layers, such as polyethylenimine ethoxylated (PEIE), which leads to the "S" shape in the current‐density characteristics of the cells. In this work, the chemical interaction between the NF active layer and the polymer interfacial layer of PEIE is deactivated by increasing its protonation. The PEIE processed from aqueous solution shows more protonated N + than that processed from isopropyl alcohol solution, observed from X‐ray photoelectron spectroscopy. NF solar cells (active layer: PCE‐10:IEICO‐4F) with the protonated PEIE interfacial layer show an efficiency of 13.2%, which is higher than the reference cells with a ZnO interlayer (12.6%). More importantly, the protonated PEIE interfacial layer processed from aqueous solution does not require a further thermal annealing treatment (only processing at room temperature). The room‐temperature processing and effective WF reduction enable the demonstration of high‐performance (12.5%) flexible NF OSCs. Abstract : Protonation of polyethylenimine ethoxylated (PEIE) can effectively passivate the chemical reaction between the PEIE and a nonfullerene (NF) active layer. As a result, the PEIE can work very efficiently as a low‐work‐function interface for NF solar cells. These flexible solar cells exhibit power conversion efficiency up to 12.5% with a room‐temperature‐processed PEIE interface.